Effect of Chemical Treatments on Mechanical Properties of Sugarcane Bagasse (Gramineae Saccharum Officinarum L) Fiber Based Biocomposites: A Review - Veena Chougala; Ashwin C. Gowda; Santhosh Nagaraja; Muhammad Imam Ammarullah (Journal of Natural Fibers)
Bagasse-based biocomposites are gaining attention for their cost-effectiveness, low density, and eco-friendly characteristics, making them suitable for applications in automotive parts, sporting goods, and household items like furniture and flooring. Despite the abundant availability of bagasse, much of it is underutilized. Converting bagasse waste into fiber-reinforced polymer composites presents a significant commercial opportunity. However, challenges such as poor wettability, high water absorption, low mechanical properties, and inadequate interfacial bonding limit their potential. Bagasse fibers typically have tensile strengths of 150–290 MPa, a Young’s modulus of 15–30 GPa, and a decomposition temperature of 200°C–240°C, with water absorption rates up to 60%. Their high cellulose content (40%–50%) and dielectric constant (3–4) also influence their compatibility with polymer matrices. Surface treatments, including mechanical, chemical, or physical methods, are necessary to enhance these properties. This review examines the impact of various chemical treatments on the mechanical, thermal, water absorption, and electrical properties of sugarcane bagasse fiber-based biocomposites, highlighting their potential and the challenges that need to be addressed for broader application.